Novel pretransplant desensitization strategies in heart transplantation - Guillaume Coutance, MD, PhD; Anita S. Chong, PhD; Marlena V. Habal, MD (JHLT Open)
Allosensitization remains a major barrier in thoracic organ transplantation, limiting access to transplantation and increasing waitlist mortality and post-transplant morbidity. Desensitization protocols aimed at improving access to transplantation and mitigating the risk of early post-transplant rejection have been developed, but current strategies have limited efficacy, and new strategies are needed. After a synthetic description of the basics of alloimmune responses leading to the production of donor-specific antibodies, the potential of novel desensitization strategies, including anti-CD38 therapies, costimulation blockade, and interleukin-6 inhibition as pretransplant desensitization therapies, are discussed in detail, including the rationale for their use, results of preclinical and clinical studies, and potential practical clinical application. Complementary novel pharmacologic (individualization therapies, combination desensitization therapies, additional perioperative antibody-risk mitigation strategies) and nonpharmacologic strategies (individual risk stratification and combination of immunologic assays) are also presented. Finally, potential next-generation therapies (bispecific T-cell engager and chimeric antigen receptor T cells) and clinical outcomes of interest are briefly discussed. Overall, this review aims to provide recent data on this constantly evolving field, while keeping in mind the clinical applicability and providing practical aspects of the use of novel pretransplant desensitization therapies.